Inter-animal genetic variability exist in organoleptic properties of prime beef meat. (March 2021) - Berry, D.P.; Conroy, S.; Hegarty, P.J.; Evans, R.D.; Pabiou, T.; Judge, M.M.
Abstract: The objective of the present study was to estimate genetic parameters for four organoleptic traits in beef meat, namely tenderness, juiciness, flavour and chewiness using data from 5380 young crossbred progeny of 748 different sires. As well as using the mean animal sensory score across all panellists for a given trait, other aggregate functions such as the median and modal values were also investigated. The heritability (SE) of mean tenderness, juiciness, flavour and chewiness was 0.16 (0.04), 0.14 (0.04), 0.11 (0.03) and 0.21 (0.06), respectively; heritability estimates for the other aggregate values of these traits were generally lower. All genetic correlations between tenderness, juiciness and flavour were positive (0.52 to 0.68) while the genetic correlations between these three traits with chewiness were all negative varying from −0.95 to −0.48. Weak genetic correlations (≤|0.16|) were evident between the sensory traits and all of carcass weight, conformation and subcutaneous fat cover. Highlights: 11% to 21% of the variability in organoleptic properties are due to genetic effects. All organoleptic properties are under similar genetic control. Weak genetic correlations exist between organoleptic properties and carcass traits.